Design of prototype for online disaster multimedia data transmission based on Android - . ROSLIDAR; YUDHA NURDIN; . NASARUDDIN (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2014)
The development of information and communication technology application is growing rapidly. It has motivated the use of mobile devices for various social networking mobile services such as android based multimedia disaster information transmission. Disaster multimedia information is important for quick response and recovery phases of the disaster management. In previous work, an online disaster information system based on location (we called it ASIKonLBS) has been proposed. However, it was only providing the coordinate information of the disaster location by using short message service (SMS) gateway and global positioning system (GPS). In this paper, we propose the design of prototype for online disaster multimedia data transmission based on android. Such that, the ASIKonLBSv2 can provide not only the information of the location, but also the situation of the disaster area including news, picture, and video. The research method refers to a spiral model that begins with conceptual design, prototype development and evaluation. The result shows that the designed prototype can be implemented for online disaster multimedia data transmission (news, photo and video) using Android Developer Tools. Furthermore, the prototype can be installed in the android-based smartphone and map the disaster multimedia data onto the web of ASIKonLBS. Therefore, the proposed prototype is useful for the disaster agencies and practitioners in order to give the first aid for the victim in the disaster area